The habit of indiscriminate spitting in betel chewing - Barus, Aguslina Wati Kristina; Hidayat, Wisnu; Bangun, Henny Arwina (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2023)
Betel nut consumption is a customary practice in Simalungun society and is frequently observed during typical and routine events. Nevertheless, there persists a group of individuals who are inclined towards crude expectoration behavior, depositing residual betel within various locations, including public domains such as markets. The focus of this investigation is to conduct an in-depth inquiry into the antecedents of such indiscriminate spitting tendencies exhibited among traders of betel nuts within the Saribudolok Traditional Market, located within the jurisdiction of the Simalungun Regency. This qualitative investigation utilized a phenomenological strategy. Seven informants were interviewed. These include betel nut sellers, visitors or purchasers, healthcare practitioners, and market managers. Observations were also made by the researchers throughout the data collection process. The triangulation technique was employed to verify all the data collected through the interviews and observations. Additionally, the researcher utilized a matrix to categorize the data based on the research objectives and questions. The data analysis followed the Miles and Huberman model, revealing that the practice of carelessly spitting betel residue among traders who consume betel is due to inadequate knowledge of healthy and hygienic living habits as well as unawareness of the dangers associated with spitting betel residue. The lack of education provided by health workers on the hazards of careless spitting and the consequent risk of disease transmission also contributes to this behavior.